Riqueza e endividamento na economia de Plantation açucareira e cafeeira: A família Teixeira Vilela-Teixeira Nogueira, Campinas, São Paulo, século XIX - Ribeiro, Maria Alice Rosa [UNESP] (FapUNIFESP (SciELO), 2015)
This paper proposes to compare the forms of the wealth and financing in the sugar- -cane and coffee economy in Campinas, Province of São Paulo in two moments - ending of the 18th century until 1850, and from 1850 to 1870. The Teixeira Vilela -Teixeira Nogueira`s family is taking as the case study. The analysis centered on two family´s members of the second and third generation, examines the formation and composition of the wealth and the different forms of credit associated to sugar-cane and coffee plantations. The documental basis comprises censuses, wills, post mortem inventories, mortgage registers, almanac.
Keywords: Campinas; Coffee economy; Credit; Financing; Sugar-cane economy; Wealth